Kecenderungan Komodifikasi dan Spasialisasi Pada Transmedia - Nur Ruli Febriyanti; Andi Faisal Bakti (CoverAge: Journal of Strategic Communication, 2017)
The political economy of communication reflects a process which commodified labor in the production process of goods and services. The political economy of the media is done by Transmedia through its television station that TransTV and Trans 7 focuses on the production, distribution, and consumption. To understand how the application of political economy approach used in the study of the mass media, then there are three concepts, namely commodification, spatialization, and structuring. As can be seen from the shape of the commodification of media content, audience, and workers. While the forms of media spatialization performed with the vertical and horizontal integration. The results of this study indicate that the media products produced two television stations tend to be geared to the world of entertainment which often do not educate. Form of commodification audience rating and share views through a program that is considered to represent the audience. Commodification of labor is done by mirroring. Mirroring performed by equating the system between the two television stations. As such, the workers can concurrently two positions or positions on two television stations. While the form of spatialization that occur in Transmedia includes vertical and horizontal integration. It can be seen that Transmedia is part of CT Corp a large company owned by Chairul Tanjung. This study also shows that the owners of the media, especially in determining the content of the medium. Some strategies acquisitions made CT Corp in creating transmedia not only as an effort to improve service to the public interest, but rather a business strategy.